PERSEPSI MAHASISWA MENGENAI SEKS BEBAS DALAM MASA PENCARIAN JATI DIRI - Ari Prasetyoaji; Anis Ameliyasari; Nurul Latifah; Depradhanti Sumarsi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
Students are in the early adult development phase, characterized by freedom to make choices, but on the other hand, they are faced with various conflicting values, such as family, religion, and social environment. This condition causes differences in how students interpret sexual experiences, both as a form of self-exploration and as a source of identity conflict. This study aims to understand students' perceptions of the phenomenon of free sex and its influence on the process of identity search. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through interviews and observations of five students using snowball sampling techniques. The results show that students have diverse perceptions of free sex, ranging from viewing it as normal behavior to an act that contradicts their values. The experience of free sex has different impacts on the process of identity formation, such as increased self-confidence, feelings of guilt, and personal value conflicts. Factors such as social environment, social media, and personal experiences also influence how students interpret this phenomenon. This study confirms that casual sex is understood personally by each individual and plays a complex role in the process of students' identity formation.